The Component Analysis of Factors Affecting Sustainable Consumption Behavior - Sintanabodee, Sintawat; Khongmalai, Orapan (Suan Dusit Graduate School Academic Journal, 2023)
This quantitative research aimed to identify the components of factors influencing sustainable consumption behavior. The sample of 500 consumers were chosen by purposive sampling who purchased green products by electronic payment. Data was gathered by an online closed-end questionnaire, which was tested by content validity and reliability method. Data analysis was performed by exploratory factor analysis (EFA) to identify common factor and create new component groups. The result revealed that factors affecting sustainable consumption behavior consisted of four factors and eight components: two components of health and environmental attitude, participation and knowledge; three components of green marketing mix 3Es, evangelism, everyplace and experience; two components of green financial innovation attributes, usability and relative advantage; and a government incentive component of incentive measures.